Accentuating technology acceptance among academicians: A conservation of resource perspective in the Malaysian context - Toh, Seong-Yuen *; Ng, Su-Ann; Phoon, Siok-Tien (Springer, 2022)
Although recent research looked at the unified theory of acceptance and use of technology (UTAUT) model among academicians, there is still lacking an adequate account for their technology adoption intentions and behaviors in the face of the COVID-19 virus. This study applies the conservation of resource (COR) theory to ground the statistical results investigating the moderation and moderated mediation effects of COVID-19 anxiety in relation to the UTAUT model. According to the COR theory, anxiety linked with the COVID-19 pandemic endangers resources such as human connections (death of friends and relatives), job security and finances, as well as physical health and psychological well-being. Since resource loss is more salient according to COR theory, academicians are more willing to employ technologies like Zoom, MS Teams, and Google Classroom since the COVID-19 threat is existential and the resource loss is eminent. To test the theory, data was collected through an anonymous survey during the months of December 2020 and January 2021. The resultant data from 215 academicians was analyzed using Hayes Process Macro in SPSS. COVID-19 Anxiety positive moderates both the direct effects of Performance Expectance-Behavior Intention and the mediating Performance Expectance-Behavior Intension-Usage relationships. Similar results were seen for other predictors, albeit the moderated mediations for Effort Expectancy and Facilitating Conditions were not significant. These findings overwhelmingly corroborate the claims that COR theory more comprehensively explains the effects of COVID19 anxiety among academicians in relation to the UTAUT model.